Lenvatinib Versus Sorafenib as First‐Line Treatment of Unresectable Hepatocellular Carcinoma: A Cost–Utility Analysis. (20th November 2019) - Kim, John J.; McFarlane, Thomas; Tully, Stephen; Wong, William W.L.
Abstract: Background: In a global, phase III, open‐label, noninferiority trial (REFLECT), lenvatinib demonstrated noninferiority to sorafenib in overall survival and a statistically significant increase in progression‐free survival in patients with unresectable hepatocellular carcinoma (HCC). Recently, lenvatinib became the first agent in more than 10 years to receive approval as first‐line therapy for unresectable HCC, along with the previously approved sorafenib. The objective of this study was to determine the comparative cost‐effectiveness of lenvatinib and sorafenib as a first‐line therapy of unresectable HCC. Materials and Methods: A state‐transition model of unresectable HCC was developed in the form of a cost–utility analysis. The model time horizon was 5 years; the efficacy of the model was informed by the REFLECT trial, and costs and utilities were obtained from published literature. Probabilistic sensitivity analyses and subgroup analyses were performed to test the robustness of the model. Results: Lenvatinib dominated sorafenib in the base case analysis. A probabilistic sensitivity analysis indicated that lenvatinib remains a cost‐saving measure in 64.87% of the simulations. However, if the cost of sorafenib was reduced by 57%, lenvatinib would no longer be the dominant strategy. Conclusion: Lenvatinib offered a similar clinical effectiveness at a lower cost than sorafenib, suggesting that lenvatinib would be a cost‐saving alternative in treating unresectable HCC. However, lenvatinib may fail to remain cost‐saving if a significantly cheaper generic sorafenib becomes available. Abstract : This article focuses on the cost‐effectiveness of lenvatinib and sorafenib as a first‐line therapy for unresectable hepatocellular carcinoma.